2003
DOI: 10.1046/j.1540-8167.2003.02305.x
|View full text |Cite
|
Sign up to set email alerts
|

Transvenous Defibrillation Leads: High Incidence of Failure During Long‐Term Follow‐Up

Abstract: Transvenous polyurethane ICD leads showed a high rate of lead insulation failure late after implantation with frequent inappropriate shock deliveries. Close follow-up is mandatory in patients with these leads. Automated device control features with patient alert function integrated into new devices may contribute to early detection of lead failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(77 citation statements)
references
References 18 publications
5
68
1
2
Order By: Relevance
“…However, routine follow-up may not detect some lead failures because 1) the defect is partial and therefore the lead problems may be intermittent, and 2) routine follow-up (usually every 3 months) may be insufficient. As previously reported, 9) ICD lead insulation failure was usually associated with normal values for impedance, sensing and pacing threshold at the time of lead failure. To detect these insulation failures, Dorwarth, et al 9) showed the importance of short RR interval (< 140 msec) nonsustained VT in stored intracardiac electrograms.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…However, routine follow-up may not detect some lead failures because 1) the defect is partial and therefore the lead problems may be intermittent, and 2) routine follow-up (usually every 3 months) may be insufficient. As previously reported, 9) ICD lead insulation failure was usually associated with normal values for impedance, sensing and pacing threshold at the time of lead failure. To detect these insulation failures, Dorwarth, et al 9) showed the importance of short RR interval (< 140 msec) nonsustained VT in stored intracardiac electrograms.…”
Section: Discussionsupporting
confidence: 63%
“…As previously reported, 9) ICD lead insulation failure was usually associated with normal values for impedance, sensing and pacing threshold at the time of lead failure. To detect these insulation failures, Dorwarth, et al 9) showed the importance of short RR interval (< 140 msec) nonsustained VT in stored intracardiac electrograms. They reported that 31 of 261 ICD patients experienced a lead related sensing failure during a mean follow-up period of 4.0 ± 2.6 years, and in 21 of 31 patients device interrogation showed short RR interval nonsustained VT 40 ± 43 days before clinically relevant lead failure.…”
Section: Discussionsupporting
confidence: 63%
“…ICD leads are significantly more complex than PM leads and must allow high voltage energy delivery for defibrillation when necessary and, may be inherently more susceptible to failure. The mechanical stress can cause fracture in a lead or failure in insulation by chronic excessive pressure on the body of the lead by the ligature used for fixation (Dorwarth et al, 2003) or the subclavian crush syndrome (Antonelli et al, 1998) or the higher activity patients or the multiple leads or the anatomic reasons in females. The insulation degradation by breakdown of polyurethane polymers due, in most cases, to metal ion oxidation like in the Medtronic models 6936 and 6966.…”
Section: Icd-specific Complicationsmentioning
confidence: 99%
“…A recent report estimated an ICD lead survival rate of only 60% after eight years, with no difference between 'older' and 'recent' models. 13,14 It has to be regretted that an independent, prospective follow-up of ICD lead performance is lacking, which would enable an educated choice of reliable lead models. A nationwide prospective registration could be instrumental in such a survey.…”
Section: Not Advisablementioning
confidence: 99%